Cloning and characterization of DNA complementary to the measles virus mRNA encoding hemagglutinin and matrix protein. - Rozenblatt, S (1982)
Since cloning and characterization of DNA complementary to measles virus mRNA encoding for the nucleocapsid protein (M. Gorecki and S. Rozenblatt, Proc, Natl. Acad, Sci, U.S.A. 77:3686--3690, 1980), two additional measles-specific clones containing different classes of sequences have been characterized. The cloned plasmids contain inserts of 480 and 530 base pairs as shown by agarose gel electrophoresis and electron microscopy. The sizes of the mRNA species complementary to these inserts are 1,700 and 1,550 nucleotides, respectively as determined by the Northern technique. The cloned DNA fragments were further identified as reverse transcripts of the mRNA coding for the glycoprotein and matrix protein of measles virus. The major cell-free translation products of mRNA selected by hybridization to the individual cloned DNAs comigrated with the 70K in vitro products and matrix proteins. One of the cell-free translation products (70K) was also immunoprecipitated specifically with monoclonal antibodies against measles virus glycoprotein.